Growth and Production of Several Corn Varieties at Various NPK Fertilizer Dosages - Yunus Musa; Muh. Farid BDR; Hari Iswoyo; Ahmad Fauzan Adzima; Nur Qalbi Zaesar M; Arna Larasati (Agrotech Journal, 2022)
Increasing corn production in Indonesia is one of the government's concerns to ensure the strengthening of food towards self-sufficiency. Improvement of fertilization methods and the use of superior varieties are parts of the intensifications to increase crop productivity. The purpose of this study was to determine the effect of NPK fertilizer doses, types of varieties, and their interactions on the growth and production of corn. This study was conducted from July to October 2022 at Bajeng Cereal Research Center (KP) Experimental Garden, Bajeng Sub-district, Gowa District, South Sulawesi at 27.2 m asl, specifically 5o18'21.5” S, 119o28' 38.6” E. The study used a split-plot design with fertilizer doses N:P: K as the main plot (P), namely N:P: K 60% = 120:90:60, N:P: K 80% = 160:120:80, N:P: K 100% = 200:150:100, N:P: K 120% = 240:180:120, and N:P: K 140% = ‎‎280:210:140. The varieties were used as subplots (V), namely Sinhas 1 (V1), Jakarin 1 (V2), Nasa 29 (V3), JH 36 (V4), ‎Bisi 18 (V5), ADV (V6), and Pioner ( V7). The results of the study showed that the combination of the fertilizer doses of N:P:K 100% = ‎‎200:150:100 with Pioner variety (P3V7) obtained the highest average yield of ‎11.81 t. ha-1 among other combinations of N:P: K fertilizer doses with varieties